Caracterização e avaliação de acessos de bucha vegetal - Medeiros, Marcelo Gurgel (2015)
This study aimed to characterize accessions and evaluate the physiological maturity in accessions of sponge gourd seeds collected in Rio Grande do Norte. The accessions belonging to the germplasm collection of cucurbits of the Plant Genetic Resources Laboratory of Universidade Federal Rural do Semi-Árido. The characterization experiments were conducted at the experimental garden and Laboratory of Plant Genetic Resources, Department of Plant Sciences of UFERSA Mossoro - RN. In the test characterization of accessions, used the an incomplete block design, consisting of two experiments in a randomized block design with four regular treatment and two treatments common to experiments, totaling ten treatments with three replications. For characterization of the accessions were applied 11 morphological descriptors: fruit weight, fiber mass, bark mass, fruit length, diameter in the lower, middle and upper portions, textured at inferior, middle and top of the fibers, and ease of release seeds. The data were subjected to joint analysis, mean comparison test Scott-Knott at 5% probability, multivariate analysis using clustering methods of Tocher and UPGMA and importance of descriptors based on generalized Mahalanobis distance using Singh method. In the study of physiological maturity in sponge gourd accessions seeds, an experiment was conducted in a seed laboratory in a completely randomized design with four replications in a factorial scheme 3x5 (three sponge gourd accessions and five seasons of harvest). In this, fruits of three accessions were harvested from the tenth day after anthesis (DAA) to the fiftieth DAA, at intervals of ten days. After each harvest was recorded fresh fruit weight, then the seeds were extracted manually fruit and subjected to the following determinations: 100 seeds, moisture content, seeds dry mass, seedling emergence and emergence speed index. There was variation among accessions studied for length and diameter of the fruits, the fiber texture, and the weight of the fruits, fiber and bark. The characterization showed genetic divergence among accessions. At ten DAA were not formed seeds observed in fruits harvested in any of the accessions. Results have show that the best physiological performance of the seeds of sponge gourd accesses, in the studied conditions, were observed at 50 DAA